The Effect Of Product Quality And Brand Image On Customer Loyalty Through Consumer Satisfaction Of Nelongso Chicken Restaurant Jember Branch - Carollyn Sherly Stepen; Hamzah Fansuri Yusuf; Bagus Qomaruzzaman Ratu Edi (LPPM Institut Teknologi dan Sains Mandala, 2021)
This study aims to determine the partial and simultaneous effect of the variable product quality and brand image on consumer loyalty through customer satisfaction at Nelongso Chicken Restaurant, Jember Branch. The data used in this study are primary data in the form of data from questionnaires and secondary data in the form of profiles from Nelongso Chicken Restaurant, Jember Branch. The data processing method in this study uses the Research Indicator Test Analysis method, namely Validity Test and Reliability Test, Classical Assumption Test, namely Normality Test, Multicollinearity Test and Heteroscedasticity Test, Path Analysis (Path Anlysis) and Hypothesis Testing, namely t-test, with the help of SPSS analysis tools 25. The results showed that the product quality variable had a significant and positive direct effect on Consumer Satisfaction at Nelongso Chicken Restaurant, Jember Branch, the Brand Image variable directly had a significant and positive effect on Consumer Satisfaction at Nelongso Chicken Restaurant, Jember Branch, the Product Quality variable directly had a significant and positive effect on Consumer Loyalty of Nelongso Chicken Restaurant, Jember Branch, Brand Image variable directly has a significant and positive effect on Consumer Loyalty of Nelongso Chicken Restaurant Jember Branch, Consumer Satisfaction variable directly has a significant and positive effect on Consumer Loyalty of Nelongso Chicken Restaurant Jember Branch, Product Quality variable through customer satisfaction Indirectly Affects significantly and positively to consumer loyalty Nelongso Chicken Restaurant Jember Branch and Brand Image variables through consumer satisfaction indirectly affect spirit significantly and positively to the Customer Loyalty of the Nelongso Chicken Restaurant Jember Branch. Keywords: Product Quality, Brand Image, Consumer Loyalty, Consumer Satisfaction.